Response of seismically isolated buildings considering poundings. - Komodromos, Petros (Earthquake engineering & structural dynamics.)
Numerical simulations and parametric studies have been used to investigate the influence of potential poundings of seismically isolated buildings with adjacent structures on the effectiveness of seismic isolation. Poundings are assumed to occur at the isolation level between the seismically isolated building and the surrounding moat wall. After assessing some common force-based impact models, a variation of the linear viscoelastic impact model is proposed to avoid tensile impact forces during detachment, while enabling the consideration of permanent plastic deformations at the vicinity of the impact. A large number of numerical simulations of seismically isolated buildings with different characteristics have been conducted under six earthquake excitations in order to investigate the influence of various design parameters and conditions on the peak floor accelerations and interstorey deflections during poundings. The numerical simulations demonstrate that poundings may substantially increase floor accelerations, especially t the base floor where impacts occur. Higher modes of vibration are excided during poundings, increasing the interstorey deflections, instead of retaining an almost rigid-body motion of the superstructure, which is aimed with seismic isolation. Impact stiffness seems to affect significantly the acceleration response at the isolation level, while the displacement response is more insensitive to the variation of the impact stiffness. Finally, the results indicate that providing excessive flexibility at the isolation system to minimize the floor accelerations may lead to a building vulnerable to poundings, if the available seismic gap is limited.